ZULKIFLI MUHAMMAD : PEMIKIRAN DAN PERJUANGAN - Kamarudin Jaffar, 1951- (Kuala Lumpur : IKDAS, 2001)
On prominent Malaysian Islamic scholar and politician, Zulkifli Muhammad; a festschrift in commemorating the 50th anniversary of Pan Malaysian Islamic Party.
'Sempena Jubli Emas PAS, 1951-2001.'--Cover.
Includes bibliographical references (p. 184).
References : page 184.
In Malay.
Keywords: Zulkifli bin Mohamed, -- 1927-1964.; Malaysia -- Politics and government; Malaysia -- Biography